Sustainable Development in Mining Communities: The Case of South Africa's West Wits Goldfield - Cole, Megan J.; Broadhurst, Jennifer L. (Frontiers in Sustainable Cities, 2022)
There is a significant role for the mining and minerals industry to play in achieving the Sustainable Development Goals (SDGs) at a global level, through supplying the raw materials needed for technological progress, human development and cleaner economic growth, and at a local level, through socio-economic development and support, environmental protection, and good governance. While mining companies support the SDGs at the corporate level, there is a lack of evidence to show whether they are being implemented at the mine site level. There is also a lack of clarity on who the mine host communities are and what happens to the SDGs commitments after mine closure. The aim of this study was to identify all the host communities in the West Wits goldfield in South Africa and measure a comprehensive set of local SDG indicators, to explore the local variations that are hidden at national and municipal level, and the implications for communities achieving the SDGs in the context of mine closure. The West Wits is home to over 300,000 people living in 47 diverse communities - towns, mine villages, townships, informal settlements, industrial areas and rural areas. While 23 local SDG indicators were selected, only 13 indicators across 8 SDGs could be measured using census data. The findings show significant inequality between communities and deprivation in many communities, particularly the informal settlements. There are low levels of education, internet access and employment across the communities, indicating high vulnerability to mine closure. Without major intervention the SDGs will not be met by 2030 and thousands of people in these communities will be left behind. This is even more concerning given the majority of mines are expected to close in the next 10 to 20 years and the local economy in the West Wits is largely reliant on mining. Achieving the SDGs will require collaboration between multiple mining companies, local government authorities, civil society and communities, and significant urgent interventions on education and skills development, internet access and employment creation beyond the mining industry.